Mathematical creative approach for enhancing mathematics achievement among secondary school students - Abdul Hamid, Nor Haniza; Kamarudin, Nurzatulshima (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Inspiring creativity through curriculum is the outcome of continuous effort in worldwide instructive change development of the 21st Century. The main purpose of this study was to examine the effects of Mathematical Creative Approach (MCA) on Mathematics achievement among secondary school students. The objective of this research study was to compare students’ achievement in Mathematics between a particular intervention group and a comparison group. A quasi-experimental research study was conducted using a total of 64 Form Four students from two urban schools in Kuala Lumpur; whereby there were 32 students in the intervention group and 32 students in the comparison group, who had been selected using purposive sampling. The research instrument was Mathematics Achievement Test (MAT). The quantitative data were analysed using both descriptive and inferential statistics. The main findings are as follows: i) there was a significant difference in the students’ achievement in Mathematics between the intervention and comparison groups. The research findings indicate that the use of Mathematical Creative Approach has tremendous educational benefits, which are important for a nation that seeks to cultivate creativity and innovation in education, particularly in improving achievements in the Mathematics subject among students in the primary schools up to tertiary levels.